An updated patent review on monoamine oxidase (MAO) inhibitors. (3rd August 2022) - Guglielmi, Paolo; Carradori, Simone; D'Agostino, Ilaria; Campestre, Cristina; Petzer, Jacobus P.
ABSTRACT: Introduction: Monoamine oxidase (MAO) inhibitors are currently used as antidepressants (selective MAO-A inhibitors) or as co-adjuvants for neurodegenerative diseases (selective MAO-B inhibitors). The research within this field is attracting attention due to their crucial role in the modulation of brain functions, mood, and cognitive activity, and monoamine catabolism. Areas covered: MAO inhibitors (2018–2021) are discussed according to their chemotypes. Structure–activity relationships are derived for each chemical scaffold (propargylamines, chalcones, indoles, benzimidazoles, (iso)coumarins, (iso)benzofurans, xanthones, and tetralones), while the chemical entities were divided into newly synthesized molecules and natural metabolites. The mechanism of action and type of inhibition are also considered. Lastly, new therapeutic applications are reported, which demonstrates the clinical potential of these inhibitors as well as the possibility of repurposing existing drugs for a variety of diseases. Expert opinion: MAO inhibitors here reported exhibit different potencies and isoform selectivity. These compounds are clinically licensed for multi-faceted neurodegenerative pathologies due to their ability to also act against other relevant targets (cholinesterases, inflammation, and oxidative stress). Moreover, the drug repurposing approach is an attractive strategy by which MAO inhibitors may be applied for the treatment of prostate cancer, inflammation, vertigo, and type 1 diabetes.